Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.chemosphere.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Vertimec® 18 EC (active ingredient abamectin) to the neotropical cladoceran Ceriodaphnia silvestrii

Abstract: The aim of the present study was to evaluate the toxicity of abamectin to the neotropical cladoceran Ceriodaphnia silvestrii. To this end, acute and chronic bioassays were conducted with the commercial formulation Vertimec® 18 EC. In addition, the toxicity of water samples taken from a microcosm experiment evaluating the effects of a single application (144μga.i./L) and two applications (2×36μga.i./L) of Vertimec® 18 EC, in the presence or absence of a tadpole species (Lithobates catesbeianus), was also assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 27 publications
1
9
0
4
Order By: Relevance
“…The effects of the insecticide Vertimec® 18 EC to the cladocera Ceriodaphnia silvestrii have also been evaluated using both acute and chronic tests (CASALI-PEREIRA et al, 2015). The acute tests revealed that a concentration of 1.47 µg a.i./L immobilized 50% of the organisms within 48 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of the insecticide Vertimec® 18 EC to the cladocera Ceriodaphnia silvestrii have also been evaluated using both acute and chronic tests (CASALI-PEREIRA et al, 2015). The acute tests revealed that a concentration of 1.47 µg a.i./L immobilized 50% of the organisms within 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Located in one of the main Brazilian's region for strawberry production, Bom Repouso has been the target of several studies, most of them endeavoring to assess the toxicity of pesticides, commonly used in Brazil for that kind of crop, like abacmectinbased pesticides, and also to evaluate any possible alterations they make to the quality of the region's waters and soils (CASALI-PEREIRA et al, 2015;VASCONCELOS et al, 2016;MENEZES-OLIVEIRA et al, 2018;NUNES et al, 2016).…”
Section: Study Locationmentioning
confidence: 99%
“…They also noted a greater and more prolonged toxicity than would be anticipated based on the laboratory toxicity data that were calculated for this test organism and reported half-life values of abamectin. Reasons that were discussed by these authors for this were (i) possible presence of other (more persistent) components in the formulation besides abamectin; (ii) a slower degradation rate in the microcosms than those listed in literature indicated in the previous paragraph; (iii) a drop in dissolved oxygen (DO) concentrations and (iv) increased ammonium levels in Vertimec® 18 EC-treated microcosms (Casali-Pereira et al 2015). Although an increase in ammonium levels was indeed noted in the SAT treatment in the days after application, ammonium levels in the other treatments containing tadpoles (CT and MAT) were also higher than those in the other treatments (p < 0.05; Fig.…”
Section: Lethal Effects Of Abamectinmentioning
confidence: 95%
“…Subsequently, a priori it was expected that this second deployment would have showed less or even no toxicity. Casali-Pereira et al (2015) used the same microcosm water as used in the present study to evaluate the toxicity to the cladoceran Ceriodaphnia silvestrii. They also noted a greater and more prolonged toxicity than would be anticipated based on the laboratory toxicity data that were calculated for this test organism and reported half-life values of abamectin.…”
Section: Lethal Effects Of Abamectinmentioning
confidence: 99%
“…Nossos resultados mostraram que os Cladocera de regiões tropicais (C.silvestrii e A alta sensibilidade de C. silvestrii aos contaminantes já foi demonstrada (COELHO e ROCHA, 2010;SUEITT et al, 2015, CASALI-PEREIRA et al, 2015, enquanto a importância do uso de organismos tropicais nativos em estudos de toxicidade também foram foco em diversas pesquisas (FONSECA e ROCHA, 2004;LOPES et al, 2007; DAAM e VAN DEN BRINK, 2010;FREITAS e ROCHA, 2011MOREIRA et al, 2014).…”
Section: Discussionunclassified